2013
DOI: 10.1038/ncomms3751
|View full text |Cite
|
Sign up to set email alerts
|

Probing single- to multi-cell level charge transport in Geobacter sulfurreducens DL-1

Abstract: Microbial fuel cells, in which living microorganisms convert chemical energy into electricity, represent a potentially sustainable energy technology for the future. Here we report the single-bacterium level current measurements of Geobacter sulfurreducens DL-1 to elucidate the fundamental limits and factors determining maximum power output from a microbial fuel cell. Quantized stepwise current outputs of 92(±33) and 196(±20) fA are generated from microelectrode arrays confined in isolated wells. Simultaneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 47 publications
(65 reference statements)
7
74
0
1
Order By: Relevance
“…Our observation that only a fraction of the cells is actively respiring at electrodes is consistent with a previous study not based on optical trapping. 26 It remains unclear whether such a percentage of actively electroderespiring cells reflects the typical heterogeneity in these cultures, or whether it stems from the particular growth procedure used in this and previous studies; our finding clearly motivates additional single cell studies of the statistical distribution in EET as a function of various growth conditions. In comparison, no EET current was detected from any of 20 ∆OMC cells tested under identical conditions, further validating our measurement system, as the outer membrane multiheme cytochromes are known to be necessary for mediating EET.…”
Section: Single Cell Extracellular Respiration Measurementsmentioning
confidence: 70%
See 1 more Smart Citation
“…Our observation that only a fraction of the cells is actively respiring at electrodes is consistent with a previous study not based on optical trapping. 26 It remains unclear whether such a percentage of actively electroderespiring cells reflects the typical heterogeneity in these cultures, or whether it stems from the particular growth procedure used in this and previous studies; our finding clearly motivates additional single cell studies of the statistical distribution in EET as a function of various growth conditions. In comparison, no EET current was detected from any of 20 ∆OMC cells tested under identical conditions, further validating our measurement system, as the outer membrane multiheme cytochromes are known to be necessary for mediating EET.…”
Section: Single Cell Extracellular Respiration Measurementsmentioning
confidence: 70%
“…Another study obtained single cell measurements of EET from a different DMRB, Geobacter sulfurreducens DL-1, using microscale Ti/Au electrode arrays. 26 When active cells transiently came into contact with these electrodes, a short circuit current of 92(±33) fA per cell was observed in about 30% of the contact events. Finally, Liu et al reported an innovative approach taking advantage of optical tweezers to attach single S. oneidensis MR-1 cells to electrodes, revealing a current output of 200 fA per cell at a working electrode potential of +200 mV vs. Ag/AgCl.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on Geobacter sulfurreducens suggested that it uses a different mechanism to transport electrons (6). Simultaneous imaging and current detection of single G. sulfurreducens in contact with a nanofabricated electrode is shown in Fig.…”
Section: Bacterial Electricitymentioning
confidence: 98%
“…In this case, the coulombic efficiency might seem a good objective measure of electroactivity being independent of cell number and also considering potential electron losses within the cell. Experimentally, even harder to determine would be the electron transfer per single cell (Liu et al, 2010; Jiang et al, 2013; Gross and El-Naggar, 2015), which from our perspective could be considered an excellent measure. On the technical scale, biomass respective number of cells, N cell , or formed product, P , is often in focus.…”
Section: From Microbial Cells To Electrochemical Cells and Back Againmentioning
confidence: 95%